2021
DOI: 10.1021/acs.jcim.0c00950
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Models to Predict Inhibition of the Bile Salt Export Pump

Abstract: Cholestatic liver injury is frequently associated with drug inhibition of bile salt transporters, such as the bile salt export pump (BSEP). Reliable in silico models to predict BSEP inhibition directly from chemical structures would significantly reduce costs during drug discovery and could help avoid injury to patients. We report our development of classification and regression models for BSEP inhibition with substantially improved performance over previously published models. We assessed the performance effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…Given a reliable and fast approximate mapping from molecule to its property value, the weighted retraining approach can optimize the latent space jointly for more practical properties that are responsible for higher attrition rate of proposed drugs. With the availability of the surrogate models for protein-ligand binding score [24], inhibition of bile salt export pump [25], our approach can optimize the latent space in producing candidate drugs that are most likely to be active against specific target without causing possible damage to the patients. In terms of computational cost, retraining the generative network multiple times may be slightly expensive for larger network compared to the one we have used.…”
Section: Discussionmentioning
confidence: 99%
“…Given a reliable and fast approximate mapping from molecule to its property value, the weighted retraining approach can optimize the latent space jointly for more practical properties that are responsible for higher attrition rate of proposed drugs. With the availability of the surrogate models for protein-ligand binding score [24], inhibition of bile salt export pump [25], our approach can optimize the latent space in producing candidate drugs that are most likely to be active against specific target without causing possible damage to the patients. In terms of computational cost, retraining the generative network multiple times may be slightly expensive for larger network compared to the one we have used.…”
Section: Discussionmentioning
confidence: 99%
“…Using AMPL it was possible to automate the training and comparisons of models using different hyperparameter settings including molecular descriptors used and machine learning methods e.g., random forests, neural networks, and XGBoost. Previous work has shown that this procedure leads to high quality models [31].…”
Section: Methodsmentioning
confidence: 99%
“…Machine learning (ML) models have become a key tool to predict compound properties from molecular structure, also known as quantitative structure–property relationship (QSPR) models. In drug discovery projects, ML-based predictions are used to select the most promising series, compounds, or chemical modifications.…”
Section: Introductionmentioning
confidence: 99%